Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Perceived Health status of Francophones and Anglophones in an official bilingual Canadian province - Bélanger, Mathieu; Bouchard, Louise; Gaboury, Isabelle; Sonier, Brigitte; Gagnon-Arpin, Isabelle; Schofield, Aurel; Bourque, Paul-Emile (Canadian Journal of Public health, 2011)
Objective: It has been reported that being part of a minority group may be negatively associated with self-perceived health. The objective of this analysis was to determine whether there are differences in perceived health between the Francophone minority and Anglophone majority in New Brunswick, the only officially bilingual province in Canada. Methods: Data from the first four primary cycles of the Canadian Community Health Survey (2001 to 2007) were obtained for 17,729 New Brunswick residents. Odds of reporting good health among Francophones and Anglophones were compared using multivariate logistic regressions accounting for age, health-related behaviours, socio-demographic variables, and medical conditions. Results: In the final models, Francophone men and women were less likely than Anglophones to report their health as being good, although these differences were not statistically significant (Odds ratio, 95% confidence interval: 0.88, 0.61–1.26; 0.71, 0.49-1.04, in men and women, respectively). Conclusion: This study suggests that being part of the linguistic minority in New Brunswick is not associated with statistically significant differences in self-perceived health.